2015
DOI: 10.1158/1538-7445.am2015-1639
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 1639: Strong synergy with APR-246 and DNA-damaging drugs in primary ovarian cancer cells

Abstract: Background: Mutations in the TP53 gene occur in at least 60% of ovarian tumors and are associated with chemoresistance and poor prognosis. APR-246 (PRIMA-1MET) is the first mutant p53-reactivating compound in clinical development and has been tested as monotherapy in hematological malignancies and prostate cancer with promising results (Lehmann et al. J Clin Oncol 30, 2012). The aim of this study was to investigate the anticancer effects of APR-246 in combination with conventional chemotherapy in cancer cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Importantly, these TP53mut leukemias were sensitive to APR-246, likely by reactivation of high levels of dysfunctional p53 accumulated in the cells. Most importantly, in line with reports in ovarian cancer, 32,39 APR-246 clearly synergized with doxorubicin in vitro, ex vivo and in vivo, re-…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Importantly, these TP53mut leukemias were sensitive to APR-246, likely by reactivation of high levels of dysfunctional p53 accumulated in the cells. Most importantly, in line with reports in ovarian cancer, 32,39 APR-246 clearly synergized with doxorubicin in vitro, ex vivo and in vivo, re-…”
Section: Discussionsupporting
confidence: 85%
“…28,29 In addition, induction of oxidative stress has been reported as a second activity of APR-246, deriving from glutathione depletion, thioredoxin reductase inhibition and other effects. [30][31][32][33] APR-246 demonstrated pre-clinical anti-tumor activity and synergism with DNAdamaging drugs in different cancers 32,[34][35][36][37][38][39] and showed very moderate side effect profiles in a first-in-man phase I/IIa clinical trial in patients with refractory prostate cancer, acute myeloid and chronic lymphocytic leukemia, multiple myeloma and lymphoma. 40 Accordingly, APR-246 is currently investigated in ovarian and esophageal cancer, myeloid neoplasms and melanoma in phase II clinical trials 7/35 (ClinicalTrials.gov).…”
Section: Introductionmentioning
confidence: 99%
“…1A). The most apparent sensitization effect was observed with APR-246 (PRIMA-1Met/Eprenetapopt) (14)(15)(16)(17)(18). Whereas, CIP2A high cells were practically insensitive to APR-246, CIP2A low HEY cells showed > 50% reduction in cell viability (Fig.…”
Section: Resultsmentioning
confidence: 93%
“…243 A recent study suggested an additional mechanism of anti-tumor activity of APR-246 through induction of oxidative stress mediated by glutathione depletion and induction of ferroptosis. 244 Preclinical studies have shown synergistic effects of APR-246 and AZA in TP53-mutated MDS and AML cells and have supported the clinical evaluation of this drug association 241 Two phase Ib/II studies have evaluated the association of Eprenetapopt with AZA; the first trial involved the enrollment of TP53-mutated MDS (with intermediate or high-risk) and AML (oligoblastic AMLs, with 20-30% of blasts); 245 the second trial involved a similar population of patients, with the exception of the admission of AML patients with any blast percentage and the administration of the two drugs Eprenetapopt and AZA for up to one year in the eventuality of a HSCT. 246 The pooled analysis of 100 patients enrolled in these two studies showed an ORR of 69%, a CR rate of 43%, a NGS TP53 mutation negativity of 40%, a MRD negativity rate of 6% and a median OS after allo-HSCT of 16.1 months.…”
Section: Classification Of Tp53-mutant Mdss and Amls And Their Compar...mentioning
confidence: 95%
“…239 This molecule displays the unique property of restoring the DNA binding capacity of p53 mutant protein and, consequently, the growth and tumorsuppressing activities of this protein. [240][241] The restoring capacity was observed for various TP53 mutants.…”
Section: Classification Of Tp53-mutant Mdss and Amls And Their Compar...mentioning
confidence: 99%